RANCANG BANGUN KONTROL KOMUNIKASI UNTUK KOORDINASI PEMINDAHAN BARANG PADA PT INDUSTRI KERETA API (PERSERO) - Setyawan, Heri Oky; Rasmana, Susijanto Tri; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2017)
The use of wireless communication devices with the industrial world is still not widely applied. A large part of the communication media between devices still use cable or other media in addition to wireless communication media that elaborate on its use. In this work we created a miniature communications for the delivery of goods as in PT INDUSTRI KERETA API (Persero) or so-called PT INKA. Currently in PT INKA delivery of goods is still done using a forklift or by human power. On delivery of the goods we used Raspberry as the control center of the system of delivery of goods and two (2) Arduino as clients who receive the control command for communication itself, we used xbee module as the wirelless medium. Based on the testing that consists of sending commands (character) the success rate was 90% in the overall control. Successful delivery is influenced by the xbee maximum distance and accuracy readings of the existing tools.Keyword: Communication , Movers, Control Coordination, Wireless, Train.